Efficacy and safety of ozanimod in multiple sclerosis: Dose-blinded extension of a randomized phase II study - Cohen, Jeffrey A; Comi, Giancarlo; Arnold, Douglas L; Bar-Or, Amit; Selmaj, Krzysztof W; Steinman, Lawrence; Havrdová, Eva K; Cree, Bruce Ac; Montalbán, Xavier; Hartung, Hans-Peter; Huang, Vivian; Frohna, Paul; et al. (Multiple sclerosis (Houndmills, Basingstoke, England), 2019)
BACKGROUND: Ozanimod, an oral immunomodulator, selectively targets sphingosine 1-phosphate receptors 1 and 5. OBJECTIVE: Evaluate efficacy, safety, and tolerability of ozanimod in relapsing multiple sclerosis. METHODS: In the RADIANCE Part A phase II study (NCT01628393), participants with relapsing multiple sclerosis were randomized (1:1:1) to once-daily ozanimod hydrochloride (0.5 or 1 mg) or placebo. After 24 weeks, participants could enter a 2-year, dose-blinded extension. Ozanimod-treated participants continued their assigned dose; placebo participants were re-randomized (1:1) to ozanimod hydrochloride 0.5 or 1 mg (equivalent to ozanimod 0.46 and 0.92 mg). RESULTS: A total of 223 (89.6%) of the 249 participants completed the blinded extension. At 2 years of the extension, the percentage of participants who were gadolinium-enhancing lesion-free ranged from 86.5% to 94.6%. Unadjusted annualized relapse rate during the blinded extension (week 24-end of treatment) was 0.32 for ozanimod hydrochloride 0.5 mg → ozanimod hydrochloride 0.5 mg, 0.18 for ozanimod hydrochloride 1 mg → ozanimod hydrochloride 1 mg, 0.30 for placebo → ozanimod hydrochloride 0.5 mg, and 0.18 for placebo → ozanimod hydrochloride 1 mg. No second-degree or higher atrioventricular block or serious opportunistic infection was reported. CONCLUSION: Ozanimod demonstrated sustained efficacy in participants continuing treatment up to 2 years and reached similar efficacy in participants who switched from placebo; no unexpected safety signals emerged.
Keywords: Multiple Sclerosis, Relapsing-Remitting; dvojitá slepá metoda; Sphingosine 1 Phosphate Receptor Modulators; MRI; indany; Double-Blind Method; mladiství; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Clinical trial; magnetická rezonanční tomografie; hodnocení výsledků zdravotní péče; Magnetic Resonance Imaging; Young Adult; oxadiazoly; ženské pohlaví; T2 lesions; Humans; Indans; Outcome Assessment, Health Care; disease-modifying therapies; modulátory receptorů sfingosin-1-fosfátu; lidé středního věku; relapsing/remitting; relabující-remitující roztroušená skleróza; Oxadiazoles; dospělí; Female; Adolescent; lidé; Male; multiple sclerosis